Coping strategies of resettled communities in Laguna, Philippines - Visco, E. S. (Compendium of Human Ecology Researches in the Philippines, 2003)
This study was conducted to determine the coping strategies of the residents from the two resettlement communities, Southville 1 and Southville 7 in Laguna. It was assumed that the absence/presence of basic social services lead to the respondents' decision to stay or leave the area. Results of the study reinforced the positive trait the Filipino has been known for - resiliency. While this sites lack the necessary social services especially on health education, and livelihood opportunities for them to survive, many were able to adapt to their respective communities. They were able to develop livelihood skills like farming, fishing and entrepreneurship. Edible landscaping was adapted to augment their food requirements. The adaptive capacity contributed to their decision to stay in their respective resettlement sites. Few respondents however, went back to work in Metro Manila and leave their families in the site. Aside from their coping strategies, to communities possible barriers to social development were also determined. In one of the site, social stratification, discrimination, social fragmentation and political conflict were found to be the barriers of social development. Generally, however, the respondents believed they were much better off now than before they were resettled.